Brodie, a Dual-Purpose Chipping and Tablestock Variety with Resistance to Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode and Partial Resistance to Pathotype Pa2/3 of the Pale Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Louise-Marie Dandurand; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2024)

Geography, environment, and colonization history interact with morph type to shape genomic variation in an Arctic fish - Sarah J. Salisbury; Robert Perry; Don Keefe; Gregory R. McCracken; Kara K. S. Layton; Tony Kess; Ian R. Bradbury; Daniel E. Ruzzante (Molecular Ecology, 2023)
Polymorphic species are useful models for investigating the evolutionary processes driving diversification. Such processes include colonization history as well as contemporary selection, gene flow, and genetic drift, which can vary between intraspecific morphs as a function of their distinct life histories. The interactive and relative influence of such evolutionary processes on morph differentiation critically informs morph‐specific management decisions and our understanding of incipient speciation. We therefore investigated how geographic distance, environmental conditions, and colonization history interacted with morph migratory capacity in the highly polymorphic fish species, Arctic Charr ( Salvelinus alpinus ). Using an 87 k SNP chip we genetically characterized recently evolved anadromous, resident, and landlocked charr collected from 45 locations across a secondary contact zone of three charr glacial lineages in eastern Canada. A strong pattern of isolation by distance across all populations suggested geographic distance principally shaped genetic structure. Landlocked populations had lower genetic diversities and higher genetic differentiation than anadromous populations. However, effective population size was generally temporally stable in landlocked populations in comparison to anadromous populations. Genetic diversity positively correlated with latitude, potentially indicating southern anadromous populations' vulnerability to climate change and greater introgression between the Arctic and Atlantic glacial lineages in northern Labrador. Local adaptation was suggested by the observation of several environmental variables strongly associating with functionally relevant outlier genes including a region on chromosome AC21 potentially associated with anadromy. Our results demonstrate that gene flow, colonization history, and local adaptation uniquely interact to influence the genetic variation and evolutionary trajectory of populations.

Lehigh, a Variety with Yellow Flesh and Resistance to the Golden Cyst Nematode and Common Scab - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2023)

Stepping stones towards Antarctica: Switch to southern spawning grounds explains an abrupt range shift in krill - Angus Atkinson; Simeon L. Hill; Christian S. Reiss; Evgeny A. Pakhomov; Gregory Beaugrand; Geraint A. Tarling; Guang Yang; Deborah K. Steinberg; Katrin Schmidt; Martin Edwards; Emilce Rombolá; Frances A. Perry (Global Change Biology, 2022)
Poleward range shifts are a global‐scale response to warming, but these vary greatly among taxa and are hard to predict for individual species, localized regions or over shorter (years to decadal) timescales. Moving poleward might be easier in the Arctic than in the Southern Ocean, where evidence for range shifts is sparse and contradictory. Here, we compiled a database of larval Antarctic krill, Euphausia superba and, together with an adult database, it showed how their range shift is out of step with the pace of warming. During a 70‐year period of rapid warming (1920s–1990s), distribution centres of both larvae and adults in the SW Atlantic sector remained fixed, despite warming by 0.5–1.0°C and losing sea ice. This was followed by a hiatus in surface warming and ice loss, yet during this period the distributions of krill life stages shifted greatly, by ~1000 km, to the south‐west. Understanding the mechanism of such step changes is essential, since they herald system reorganizations that are hard to predict with current modelling approaches. We propose that the abrupt shift was driven by climatic controls acting on localized recruitment hotspots, superimposed on thermal niche conservatism. During the warming hiatus, the Southern Annular Mode index continued to become increasingly positive and, likely through reduced feeding success for larvae, this led to a precipitous decline in recruitment from the main reproduction hotspot along the southern Scotia Arc. This cut replenishment to the northern portion of the krill stock, as evidenced by declining density and swarm frequency. Concomitantly, a new, southern reproduction area developed after the 1990s, reinforcing the range shift despite the lack of surface warming. New spawning hotspots may provide the stepping stones needed for range shifts into polar regions, so planning of climate‐ready marine protected areas should include these key areas of future habitat.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Waneta, a Variety with Excellent Chip Color out of Cold Storage, Long Tuber Dormancy, and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2020)

Limited genetic parallelism underlies recent, repeated incipient speciation in geographically proximate populations of an Arctic fish ( Salvelinus alpinus ) - Sarah J. Salisbury; Gregory R. McCracken; Robert Perry; Donald Keefe; Kara K.S. Layton; Tony Kess; Cameron M. Nugent; Jong S. Leong; Ian R. Bradbury; Ben F. Koop; Moira M. Ferguson; Daniel E. Ruzzante (Molecular Ecology, 2020)
The genetic underpinnings of incipient speciation, including the genomic mechanisms which contribute to morphological and ecological differentiation and reproductive isolation, remain poorly understood. The repeated evolution of consistently, phenotypically distinct morphs of Arctic Charr ( Salvelinus alpinus ) within the Quaternary period offer an ideal model to study the repeatability of evolution at the genomic level. Sympatric morphs of Arctic Charr are found across this species' circumpolar distribution. However, the specific genetic mechanisms driving this morph differentiation are largely unknown despite the cultural and economic importance of the anadromous morph. We used a newly designed 87k SNP chip to investigate the character and consistency of the genomic differences among sympatric morphs within three recently deglaciated and geographically proximate lakes in Labrador, Canada. We found genetically distinct small and large morph Arctic Charr in all three lakes consistent with resident and anadromous morphs, respectively. A degree of reproductive isolation among sympatric morphs is likely given genome‐wide distributions of outlier SNPs and high genome‐wide F ST s. Across all lakes, outlier SNPs were largely nonoverlapping suggesting a lack of genetic parallelism driving morph differentiation. Alternatively, several genes and paralogous copies of the same gene consistently differentiated morphs across multiple lakes suggesting their importance to the manifestation of morphs. Our results confirm the utility of Arctic Charr as a model for investigating the predictability of evolution and support the importance of both genetic parallelism and nonparallelism to the incipient speciation of Arctic Charr morphs.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Lamoka, a Variety with Excellent Chip Color Out of Cold Storage and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2017)

A portrait of a sucker using landscape genetics: how colonization and life history undermine the idealized dendritic metapopulation - Sarah J. Salisbury; Gregory R. McCracken; Donald Keefe; Robert Perry; Daniel E. Ruzzante (Molecular Ecology, 2016)
Dendritic metapopulations have been attributed unique properties by in silico studies, including an elevated genetic diversity relative to a panmictic population of equal total size. These predictions have not been rigorously tested in nature, nor has there been full consideration of the interacting effects among contemporary landscape features, colonization history and life history traits of the target species. We tested for the effects of dendritic structure as well as the relative importance of life history, environmental barriers and historical colonization on the neutral genetic structure of a longnose sucker ( Catostomus catostomus ) metapopulation in the Kogaluk watershed of northern Labrador, Canada. Samples were collected from eight lakes, genotyped with 17 microsatellites, and aged using opercula. Lakes varied in differentiation, historical and contemporary connectivity, and life history traits. Isolation by distance was detected only by removing two highly genetically differentiated lakes, suggesting a lack of migration–drift equilibrium and the lingering influence of historical factors on genetic structure. Bayesian analyses supported colonization via the Kogaluk's headwaters. The historical concentration of genetic diversity in headwaters inferred by this result was supported by high historical and contemporary effective sizes of the headwater lake, T‐Bone. Alternatively, reduced allelic richness in headwaters confirmed the dendritic structure's influence on gene flow, but this did not translate to an elevated metapopulation effective size. A lack of equilibrium and upstream migration may have dampened the effects of dendritic structure. We suggest that interacting historical and contemporary factors prevent the achievement of the idealized traits of a dendritic metapopulation in nature.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Development of 26 novel microsatellite makers for the round whitefish (Prosopium cylindraceum) and successful polymorphic cross-specific amplification of seven previously developed salmonid markers - Gregory R. McCracken; Kristen L. Wilson; Hilary T. Brewis; Meghan C. McBride; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Development and characterization of 36 novel microsatellite markers for lake chub (Couesius plumbeus) using illumina paired-end sequencing - Gregory R. McCracken; Hilary T. Brewis; Meghan C. McBride; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Development of 17 novel microsatellite markers for the longnose sucker (Catostomus catostomus) and successful cross-specific amplification of 14 previously developed markers from congeneric species - Gregory R. McCracken; Kristen L. Wilson; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Development of candidate gene markers associated to common bacterial blight resistance in common bean - Chun Shi; Kangfu Yu; Weilong Xie; Gregory Perry; Alireza Navabi; K. Peter Pauls; Phillip N. Miklas; Deidré Fourie (Theoretical and Applied Genetics, 2012)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Primary Productivity in 20-year Old Created Wetlands in Southwestern Virginia - Robert B. Atkinson; James E. Perry; Gregory B. Noe; W. Lee Daniels; John Cairns (Wetlands, 2010)

Tree canopy effect on grass and grass/legume mixtures in eastern Nebraska - Michael E. L. Perry; Walter H. Schacht; Gregory A. Ruark; James R. Brandle (Agroforestry Systems, 2009)

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Impulsivity (delay discounting) as a predictor of acquisition of IV cocaine self-administration in female rats - Jennifer L. Perry; Erin B. Larson; Jonathan P. German; Gregory J. Madden; Marilyn E. Carroll (Psychopharmacology, 2005)